1999
DOI: 10.1111/j.1365-2621.1999.tb09864.x
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Utilization of Pork from an Advanced Meat Recovery System

Abstract: Pork trim from an advanced meat recovery system, referred to as pork trim-finely textured (PTFT), was characterized and compared to 80% lean ground pork (GP) and knife trimmed lean (KT). PTFT (0, 5, 10, 15%) was incorporated into 10% and 20% fat ground pork patties. PTFT had higher total pigment, cholesterol, iron and calcium and lower collagen than GP or KT. Fat content of PTFT was similar to GP and KT. PTFT increased redness and juiciness and decreased hardness, chewiness and cohesiveness of ground pork patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…The fat component, which is less pigmented and at a higher concentration in the 20% fat patties, was likely more influenced by the highly pigmented PTFT compared to the 10% fat patties. The PTFT caused a linear increase in a* values (PϽ0.05; Table 1) as was reported in our previous work with PTFT (Calhoun et al, 1999). We attributed the increased redness to the elevated total pigment content and low connective tissue content of PTFT as had been reported by Field (1975Field ( , 1988 in meat from earlier versions of recovery machines.…”
Section: Patty Studysupporting
confidence: 84%
See 2 more Smart Citations
“…The fat component, which is less pigmented and at a higher concentration in the 20% fat patties, was likely more influenced by the highly pigmented PTFT compared to the 10% fat patties. The PTFT caused a linear increase in a* values (PϽ0.05; Table 1) as was reported in our previous work with PTFT (Calhoun et al, 1999). We attributed the increased redness to the elevated total pigment content and low connective tissue content of PTFT as had been reported by Field (1975Field ( , 1988 in meat from earlier versions of recovery machines.…”
Section: Patty Studysupporting
confidence: 84%
“…Previous work with PTFT (Calhoun et al, 1999) showed increased sensory juiciness in ground pork containing up to 15% PTFT which was attributed to the increased surface area and expressible moisture of PTFT. Patties in that study were stored frozen and evaluated within 2 wk of manufacture.…”
Section: Patty Studymentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, the carcass' physiological inherent characteristics such as lipid oxidation potential and pH fluctuations occurring during pork processing procedures can limit food product stability. [27,28] Future research should integrate whole genome sequencing techniques to assess the diversity of microbial population and their impact on limiting or accelerating spoilage rates in food products. The ground pork samples were analyzed within 24 hours of the grinding procedures, and a greater emphasis on investigating product subsamples over several days following grinding may provide more useful baseline data on any shifts in the microbiota and potential intervention strategies to limit spoilage and proliferation of foodborne pathogens.…”
Section: Pyrosequencing Data Analysismentioning
confidence: 99%
“…Podobną zależność w MDOM wykazali Al-Najdawi i Abdullah (2). W MOM wieprzowym zawartość cholesterolu w porównaniu z mięsem wieprzowym wykrawanym ręcznie była znacznie wyższa i wynosiła, odpowiednio, 101,67 mg/100 g i 72,33 mg/100 g. Natomiast w mięsie wieprzowym mielonym średnia zawartość cholesterolu wynosiła 62,33 mg/100 g (8).…”
Section: Artykuł Przeglądowy Reviewunclassified